Serum Homocysteine Levels in Patients with Ischemic Heart Disease and Normal Individuals: A Comparative Study - Safdar, Laibah; Ismail, Tariq; Siddiqi, Fuad Ahmad; Amjad, Aqsa; Saeed, Sidra; Amjad, Ammara (Journal of Rawalpindi Medical College, 2025)
Objective: To compare the serum homocysteine levels of patients with ischemic heart disease (IHD) with those of normal individuals (those without ischemic heart disease) in our population. Methods: This is a case-control study, carried out at CMH Rawalpindi during the course of 6 months from June 2024 to Dec 2024. This study included 200 individuals, among whom 130 were patients with ischemic heart disease (angiographically diagnosed coronary artery disease), within the last 3 months, and 70 normal individuals (those without ischemic heart disease), with the closest matching of baseline characteristics with the cases, which comprised the control group. Individuals having other diseases or medications that could raise serum homocysteine levels were excluded from the study. Fasting serum homocysteine levels were measured in both groups and compared. Results: Mean serum homocysteine levels in patients with ischemic heart disease were higher (23.12 ± 7.16 μmol/L) as compared to normal individuals (9.60 ± 3.17 μmol/L). This difference was statistically significant, with a p-value less than 0.05. Conclusion: This study demonstrates that patients with ischemic heart disease have higher serum homocysteine levels as compared to normal individuals, suggesting a potential role of homocysteine in the pathogenesis of ischemic heart disease. These findings highlight the importance of serum homocysteine measurement in the risk assessment and management of ischemic heart disease patients. Keywords: Coronary artery disease, Homocysteine, Risk factor